Analisis Pengelolaan dan Pengendalian Piutang Pada Unit Pengelola Kegiatan (UPK) Kecamatan Ponggok Kabupaten Blitar - Berti Dila Septiana; Sura Klaudia; Kristya Damayanti; Tetty Widiyastuti (LPMP Imperium, 2021)
Poverty is one of the problems that often occurs in Indonesia. Therefore, through the Unit Pengelola Kegiatan (UPK), the government made a Simpan Pinjam Perempuan (SPP) program in revolving funds provided without any collateral, so the risk that often occurs is bad credit arrears. This causes a decrease in assets or a deficit and an increasing number of bad debts, so good management and control are needed to reduce the number of complex or uncollectible receivables. The purpose of this paper is to identify and analyze the role of management and control applied by the UPK Ponggok District, Blitar Regency, in minimizing bad debts. This research is qualitative research with data collection methods with interviews and documentation. The results of this study indicate that (1) Receivable management applied by the UPK Ponggok Subdistrict, Blitar Regency is quite good, especially in credit standards, credit requirements, and applied receivable collection policies, but in the receivables management applied there is no receivables measurement ratio policy. (2) The control of receivables that was implemented did not go well because there were still various irregularities and discrepancies between the implementation and the applicable Standard Operating Procedure.